Functional Castration from Blunt-force Trauma to Motorcycle Gas Tank from a Car-versus-motorcycle MVA - Garcher, Damian (Translation: The University of Toledo Journal of Medical Sciences, 2019)
We present a case of bilateral testicular rupture with significant extrusion and seminiferous tubule loss in an otherwise healthy 26-year-old male as the result of a car-versus-motorcycle accident. The patient was the lone driver of a motorcycle that was T-boned, resulting in significant scrotal trauma necessitating operative intervention. Because of this, he developed subsequent severe hypogonadism, which improved with exogenous testosterone administration. We undertook a literature review, which revealed that blunt trauma is an extremely uncommon cause of acquired hypogonadism.